ANALISIS LAGU NO WOMAN NO CRY OLEH BOB MARLEY MELALUI PENDEKATAN SOSIOLOGI SASTRA - Awom, Iriano Yedija Petrus (Universitas Papua, 2017)
âNo Woman, No Cryâ is one of Bob Marleyâs popular songs besides âI Shot the Sherriff,â âOne Love,â âIs This Love,â and âThree Little Birds.â This song is worth studied since it often creates a sense of dualism and ambiguous in the meaning among fans especially the non-Jamaican audience. Despite the fact that the language of the lyric is clear but in order to have an in-depth understanding one needs to have a fit and proper approach. This is because of the locality of the context through language and cultural convention. Therefore in this research the writer offers an approach through the lense of sociology of literature which emphasize the knowledge of biography and socio-history. This approach is being conducted first by analysis of the text through heurestic and hermeneutic method. Heurestic is the first reading process that aims at giving meaning to the text based on the convention of language structures. While hermeneutic is the process of interpreting and forseeing the implied meaning of the text using all sources of knowledge. This second step can be fulfilled if the interpreter have an adequate biographical and socio-historical knowledge about the writer/author. This is in line to Hypolite Taine theory of race, moment and millieu. That a literary text is a depiction of reality from a certain community in a certain moment and millieu or circumtance.